Pustaka Negeri Sarawak / Nurul Hidayah Abdul Hai - Abdul Hai, Nurul Hidayah (Universiti Teknologi MARA, Sarawak, 2014)
Sarawak State Library also known as Pustaka Negeri Sarawak was established and opens to the public on 2nd January 2000 (Pustaka Negeri Sarawak, 2014). The establishment of Pustaka Negeri Sarawak were based on Law of Sarawak, Chapter 29, Sarawak State Library Ordinance 1999. Pustaka Negeri Sarawak plays an important part in serving the information needs of 27 distinct indigenous ethnic groups that speak 45 different languages and dialects. In addition, this state library conceived as a major information resource centre and as the hub of information services for the public and private sectors. It links libraries, archives and information centres elsewhere in Sarawak and throughout Malaysia. It also provides a gateway into and from publicly accessible international information centres. Moreover, Pustaka Negeri Sarawak is a beautifully designed building in an extensive park with a collection of sophisticated specialized services. There are several facilities provided to the visitors easy for them do their own activities. Pustaka Negeri Sarawak was located at Jalan Pustaka, Off Jalan Stadium Petrajaya which is within a vast park covers the State Mosque (Masjid Besar Jamek) and the Minaret Gardens on the western side. Pustaka Negeri Sarawak expands their wings by opening new branches which are State Record Repository, Jalan Cahya Indah, Off Jalan Sultan Tengah and Pustaka Negeri Sarawak Miri, Jalan Kipas, Miri City Fan. The landscape of Pustaka Sarawak is beautiful and easy for the visitors to do their activity which includes a lake, areas for public performances and art exhibitions, a playground, picnic areas, a scenic drive, pedestrian walkways and bicycle lanes strewn with trees, shrubs and flower gardens. As usually in the evening the visitors come to Pustaka Sarawak on a purpose to do healthy activities such as jogging, cycling, aerobics, fishing and plays football. Besides that, there are some facilities in the Pustaka Sarawak can be used by the public such as Exhibition Gallery as a wedding venue and other events, Children Infotheque is for the kids to learn something new in the comfortable place.